2019
DOI: 10.1002/pd.5431
|View full text |Cite
|
Sign up to set email alerts
|

Variants in the 5'‐UTR of APELA gene in women with preeclampsia

Abstract: Objective To detect APELA gene variants in clinical cases with preeclampsia (PE) and evaluate the influence of the APELA variants in gene expression. Method A total of 288 individuals suffering from PE and 384 unaffected individuals were chosen for case‐control studies. Genomic DNA was extracted from peripheral blood. Variants screening of APELA gene was conducted, and potential influence of variants in APELA expression was evaluated with a luciferase assay. Results Two rare variants (c.‐306A > G and c.‐145A >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Consistent with prior studies, the downregulation of APELA has been associated with vascular constriction and the development of micro-and macrovasculature disorders, including conditions such as preeclampsia (20) and pulmonary artery disease in individuals with chronic lung diseases (21). This observation aligns with epidemiological reports indicating an elevated risk of preeclampsia in pregnancies at higher altitudes (22), and arterial remodeling in dwellers with chronic exposure to these settings (23).…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with prior studies, the downregulation of APELA has been associated with vascular constriction and the development of micro-and macrovasculature disorders, including conditions such as preeclampsia (20) and pulmonary artery disease in individuals with chronic lung diseases (21). This observation aligns with epidemiological reports indicating an elevated risk of preeclampsia in pregnancies at higher altitudes (22), and arterial remodeling in dwellers with chronic exposure to these settings (23).…”
Section: Discussionsupporting
confidence: 88%
“…Yang et al reported that rare variants in the 5′-UTR of the APELA gene were associated with PE, but there have been no studies to date indicating a relationship between the APELA gene and HDPs through a haplotype-based case-control study [ 31 ]. The HDP-sensitive haplotype identified in the present study might affect variants in APELA that cause a genetic disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Another study stated that protein transcription could be reduced in women expressing rare variants of the Elabela gene, and it was suggested that this could cause an increased risk of pre-eclampsia 20 .…”
Section: Discussionmentioning
confidence: 99%